(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic brought uncertainties to the social, economic and political scenario, leading to extraordinary challenges to firms. This paper sheds light on how the home office adaptation affects the Quality of Work Life (QWL). We conducted an experiment with 322 participants to understand the mechanism by which tests the effect of home office adaptation on the QWL. Our results point out that companies that adapted better to home office positively impact the participants’ perception of QWL. We expect to contribute to the organizational theory and human resources field by providing empirical data about the adaptation to the home office and expectation of QWL. Furthermore, we provide evidence to practitioners who may get advantage of our experimental strategy to suit their firms better to this new scenario.